Vouchers for Basic Education in Developing Countries : A Principal-Agent Perspective - Gauri, Varun; Vawda, Ayesha (World Bank, Washington, DC, 2014)
Voucher programs consist of three simultaneous reforms: (1) allowing parents to choose schools, (2) creating intense incentives for schools to increase enrollment, and (3) granting schools management autonomy to respond to demand. As a result, voucher advocates and critics tend to talk past each other. A principal-agent framework clarifies the argument for education vouchers. Central findings from the literature, including issues related to variance in the performance measure, risk aversion, the productivity of more effort, multiple tasks, and the value of monitoring are found relevant for an analysis of vouchers. An assessment of findings on voucher programs in industrial countries, as well as a review of voucher or quasi-voucher experiences in Bangladesh, Chile, Colombia, Cote d'Ivoire, and the Czech Republic support the usefulness of the analytic framework. The authors conclude that vouchers for basic education in developing countries can enhance outcomes when they are limited to modest numbers of poor students in urban settings, particularly in conjunction with existing private schools with surplus capacity. The success of more ambitious voucher programs depends on an institutional infrastructure challenging to industrial and developing countries alike.